CARBON TRADING AND MANGROVE FORESTS: MEASURING THE ECONOMIC VALUE OF “BLUE CARBON” AS A NEW ASSET IN LOW CARBON DEVELOPMENT POLICY - Ahmet Demir; Zeynep Toprak; Cemil Kaya (Journal of Selvicoltura Asean, 2025)
The global imperative for low-carbon development necessitates the formal integration of Nature-based Solutions. Mangrove forests, known for their superior carbon sequestration as “Blue Carbon,” offer a crucial asset, yet their economic potential remains severely constrained by valuation and policy standardization issues. This study aimed to develop a standardized Total Economic Valuation (TEV) framework for Indonesian Blue Carbon and analyze the regulatory requirements for its formal inclusion in the national carbon trading policy. A mixed-methods design utilized biophysical data from two major mangrove regions, employing financial modeling (Discounted Cash Flow and Monte Carlo simulations) to calculate TEV, and policy analysis to assess governance readiness. The TEV averaged USD 21,500 ha, nearly three times the carbon-only value, demonstrating the asset’s premium quality and superior financial stability (45% lower IRR volatility). However, a significant governance bottleneck was identified (Policy Alignment Index 65%), primarily due to a centralized Monitoring, Reporting, and Verification (MRV) system and uncertain community benefit sharing, which actively inhibits market entry. Blue Carbon is validated as a high-integrity, de-risked asset, but its realization depends critically on policy intervention, urging the immediate adoption of the TEV framework and the decentralization of MRV to ensure social equity and accelerate climate finance.